O GÊNERO NURSERY RHYMES EM TRANSPOSIÇÃO DIDÁTICA - POLEZE, GERSON ANSCHAU (2021)
Faced with the necessity for more studies that focus on additional languages teaching in kindergarten (KG), giving the few number of research projects on the subject (TONELLI; PÁDUA, 2016), this study aims at investigating the comprehension and oral (re)production of KG students when engaging in language practices through a Didactic Sequence (DS) focusing on the nursery rhymes (NR) oral genre in English (EN). Our specific objectives are: a) To describe the Didactic Model (DM) of the NR genre through the scrutiny of twenty samples according to the levels of analysis of the Sociodiscursive Interactionism (SDI); b) To describe and analyze a DS produced to work with NR; evidencing its macrostructure, as well as the language capacities and operations that the consignments enhance; c) To analyze which are the language capacities mobilized by the students during first and final (re)productions, as well as on intermediate assessments. To achieve it, we start from the assumptions of the SDI (BRONCKART, 1999) and propose the insertion of a DS (SCHNEUWLY; DOLZ, 2004) about NR for teaching EN at KG. In the next sections, the origins on KG and its current paradigms as the first stage of basic education (KUHLMAN JR., 2010; OLIVEIRA, 2011) are presented; we made a survey on the state of the art research on teaching EN at KG; we dissertated about Vigotsky social interactionism (1991, 2009) and the main principles of SDI; we covered the DM and DS devices; proposed intermediate assessments focusing teaching orality at KG; and also wrote about the NR. Data generation occurred from the samples of the genre within the DM, language capacities shown in the DS, and also from class recording and the diagnosis of students’ initial language capacities and those potentialized at the end of the (re)productions. Results pointed out the taught dimensions of the NR genre and the possibility of didactic transposition (SCHNEUWLY, 2009; STUTZ, 2012) of those knowledges to the school class, the predominant capacities in the DS, especially those of Signification, Action and Multissemiotic, around twenty-eight activities organized in four modules, one initial and final (re)production and two intermediate assessments. Results of the evaluations show that the (re)productions contributed to expand the initial capacities of students, strengthening operations related to engaging on language activities through the NR genre (3SC), understanding the overlap between language and praxiological activities (6SC), mobilization of world knowledge for understanding and/or (re)production of NR (4AC), understanding of the relationships between verbal and non-verbal genre elements (1MSC), as well as its semiotic elements (5MSC). Finally, the implementation of the DS focusing on NR provided interaction among students through EN, showing a significant apprehension of language.